Functionalization of oxide-free silicon surfaces - DeBenedetti, William J. I.; Chabal, Yves J. (Journal of vacuum science & technology. A, Vacuum, surfaces, and films, 2013)
Much of the microelectronic industry and many uses of silicon are based on the stability of silicon oxide and the electrical quality of its interface with the silicon substrate. It is natural therefore to have focused on functionalizing silicon by grafting molecules on its oxide. However, severe issues are associated with organic functionalization of silicon oxide, such as reproducibility in grafting the layers and quality and stability of these layers once grafted. These problems have stimulated recent efforts to prepare and functionalize high quality oxide-free silicon surfaces. In this review, methods for transforming such oxide-free, hydrogen-terminated silicon surfaces are presented, including hydrosilylation (the formation of silicon carbon bonds) and direct replacement of hydrogen by reactive leaving groups (halogens, methoxy, and hydroxyl). These efforts are based on a number of complementary characterization methods, such as infrared absorption and x-ray photoelectron spectroscopy, low energy ion scattering, and capacitance/current voltage measurements. In contrast to previous work on the subject, the focus of this review is on controlled defects on Si(111) surfaces with aim to better understand the surface structure of silicon nanoparticles, the smallest Si object with the highest number of defects. To that end, sections on preparation and selective functionalization of stepped silicon surfaces are included, and the current characterization and understanding of silicon nanoparticles added. The outlook on where the field may be going is presented.